Arthroscopic coracoclavicular button fixation versus anatomic locking plate fixation for unstable distal clavicular fractures. - Erden, Tunay; Kapicioglu, Mehmet; Ersen, Ali; Toker, Berkin; Sahin, Koray; Bilsel, Kerem (My University, 2021)
Neer type II distal clavicle fractures are unstable and associated with high nonunion rates. The aim of this retrospective study was to compare the clinical and radiographic outcomes of anatomic locking plate fixation and arthroscopic coracoclavicular button fixation for unstable distal clavicle fractures.

Forty-seven patients with Neer type II distal clavicle fractures were treated surgically using either anatomic locking plate fixation (group 1, n = 20) or all arthroscopic coracoclavicular button fixation (group 2, n = 27) between 2012 and 2019 in 2 centers. Clinical and radiographic outcomes after an average follow-up period of 49 months for group 1 and 32 months for group 2 were assessed using the American Shoulder and Elbow Surgeons Shoulder score, Constant-Murley score, visual analog scale score and X-rays.

At the final follow-up, the mean American Shoulder and Elbow Surgeons Shoulder score, Constant-Murley score, and visual analog scale score for group 1 and group 2 were 92.5 ± 3.9 (range 88.3-98.3), 93.6 ± 4.0 (range 90-100), and 0.6 ± 0.6 (range 0-2) and 95 ± 3.3 (range 86.6-100), 96.2 ± 3.0 (range 88-100), and 0.4 ± 0.5 (range 0-1), respectively ( = .32,  = .15, and  = .59, respectively). At the final follow-up, acceptable reduction and bone healing were achieved in all patients. All patients in both groups were able to resume work as well as sports activities. Postoperative complications included 1 case of acromioclavicular joint arthritis and 1 case of screw penetration in group 1 and 2 cases of coracoid process fracture that did not require additional surgery in group 2. Five patients underwent hardware removal owing to skin irritation and dissatisfaction with the cosmetic appearance in group 1.

Both distal anatomic locking plate fixation and arthroscopic coracoclavicular button fixation provide satisfactory functional and radiological outcomes. Both procedures can be used to treat distal clavicle fractures because they have a minimal risk of complications and present similar, high union rates.
Keywords: Arthroscopic treatment; Coracoclavicular; Cortical suture button; Distal clavicle fracture; Locking plate; Shoulder arthroscopy